Revisiting the empirical case against perceptual modularity - Masrour, Farid; Nirshberg, Gregory; Schon, Michael; Leardi, Jason; Barrett, Emily (Frontiers in Psychology, 2015)
Some theorists hold that the human perceptual system has a component that receives input only from units lower in the perceptual hierarchy. This thesis, that we shall here refer to as the encapsulation thesis, has been at the center of a continuing debate for the past few decades. Those who deny the encapsulation thesis often rely on the large body of psychological findings that allegedly suggest that perception is influenced by factors such as the beliefs, desires, goals, and the expectations of the perceiver. Proponents of the encapsulation thesis, however, often argue that, when correctly interpreted, these psychological findings are compatible with the thesis. In our view, the debate over the significance and the correct interpretation of these psychological findings has reached an impasse. We hold that this impasse is due to the methodological limitations over psychophysical experiments, and it is very unlikely that such experiments, on their own, could yield results that would settle the debate. After defending this claim, we argue that integrating data from cognitive neuroscience resolves the debate in favor of those who deny the encapsulation thesis.